1996
DOI: 10.1074/jbc.271.22.12840
|View full text |Cite
|
Sign up to set email alerts
|

α-Branched 1,2-Diacyl Phosphatidylcholines as Effectors of Activity of Cytochrome P450SCC (CYP11A1)

Abstract: We synthesized phosphatidylcholines with fully saturated branched fatty acyl chains substituted in the 2-positions of the main chains and studied the influence of these lipids on the activity and other properties of P450SCC in vesicle-reconstituted systems. These saturated branched lipids, with regard to the fatty acyl moiety in molecular shape similar to cardiolipin but with the headgroup of phosphatidylcholines retained, showed a stimulatory efficiency higher than any other phospholipid and at least comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
(80 reference statements)
3
21
0
Order By: Relevance
“…nary results obtained in DOPC vesicle systems suggested that the stimulation of P450SCC activity by branched PCs is correlated with the fraction of the enzyme in the high spin form (8) as has been discussed earlier for CL and other activator lipids (5-7). The complexation of CHL with P450SCC causes a conversion of heme iron from the low spin to the high spin form, which can be monitored in the Soret region of the absorption spectrum (17,6).…”
Section: Effect Of Branched Pcs and CL On Chl Binding To P450scc In Tmentioning
confidence: 74%
See 3 more Smart Citations
“…nary results obtained in DOPC vesicle systems suggested that the stimulation of P450SCC activity by branched PCs is correlated with the fraction of the enzyme in the high spin form (8) as has been discussed earlier for CL and other activator lipids (5-7). The complexation of CHL with P450SCC causes a conversion of heme iron from the low spin to the high spin form, which can be monitored in the Soret region of the absorption spectrum (17,6).…”
Section: Effect Of Branched Pcs and CL On Chl Binding To P450scc In Tmentioning
confidence: 74%
“…To facilitate direct comparison of the results with previ-ous data, values were normalized to 100% maximum activity. The 100% value correspond to 5.8, 6.0, 6.5, 4.6, 5.3 nmol pregnenolone/min/nmol P450SCC for DMPC/PC(10,6), DMPC/ PC (12,8), DMPC/PC(14,10), DMPC/CL, and DOPC/PC(14,10), respectively. In DMPC vesicles, the rate of pregnenolone formation increases with the proportion of PC(14,10) from a turnover number of 0.45 min Ϫ1 in the absence of PC(14,10) to 6.5 min Ϫ1 with 47 mol % PC (14,10).…”
Section: Stopped Flow Kinetics Of Incorporation Of P450scc Into Vesicmentioning
confidence: 99%
See 2 more Smart Citations
“…activity depends on vesicle size in a manner related to membrane curvature (Madden et al, 1984;Schwarz et al, 1996). Respiration in mitochondria and photosynthesis in chloroplasts vary with osmotic membrane stretch (Mathai et al, 1993), and chloroplast membranes exhibit MS ion fluxes (Kikuyama and Tazawa, 2001) and swelling sensitive rates of photosynthesis (Paillotin et al, 1998).…”
Section: Leaks Pumps and Tension In A Protocellmentioning
confidence: 99%